Effects of a physical education intervention on cognitive function in young children: randomized controlled pilot study - Watson Christine; Tomporowski Phillip; Paton James Y; Boyle James ME; Fisher Abigail; McColl John H; Reilly John J (BMC, 2011)
Abstract Background Randomized controlled trials (RCT) are required to test relationships between physical activity and cognition in children, but these must be informed by exploratory studies. This study aimed to inform future RCT by: conducting practical utility and reliability studies to identify appropriate cognitive outcome measures; piloting an RCT of a 10 week physical education (PE) intervention which involved 2 hours per week of aerobically intense PE compared to 2 hours of standard PE (control). Methods 64 healthy children (mean age 6.2 yrs SD 0.3; 33 boys) recruited from 6 primary schools. Outcome measures were the Cambridge Neuropsychological Test Battery (CANTAB), the Attention Network Test (ANT), the Cognitive Assessment System (CAS) and the short form of the Connor's Parent Rating Scale (CPRS:S). Physical activity was measured habitually and during PE sessions using the Actigraph accelerometer. Results Test- retest intraclass correlations from CANTAB Spatial Span (r 0.51) and Spatial Working Memory Errors (0.59) and ANT Reaction Time (0.37) and ANT Accuracy (0.60) were significant, but low. Physical activity was significantly higher during intervention vs. control PE sessions (p < 0.0001). There were no significant differences between intervention and control group changes in CAS scores. Differences between intervention and control groups favoring the intervention were observed for CANTAB Spatial Span, CANTAB Spatial Working Memory Errors, and ANT Accuracy. Conclusions The present study has identified practical and age-appropriate cognitive and behavioral outcome measures for future RCT, and identified that schools are willing to increase PE time. Trial registration number ISRCTN70853932 (http://www.controlled-trials.com)